Is the relationship between parental abuse and mobile phone dependency (MPD) contingent across neighborhood characteristics? A multilevel analysis of Korean Children and Youth Panel Survey - Kim, Harris Hyun-soo; Chun, JongSerl (PloS one, 2018)
Research indicates that mobile phone dependency (MPD) is associated with various behavioral and internalizing problems. While a significant amount of findings points to its negative outcomes, there is a dearth of evidence concerning the determinants of MPD. This study focuses on this critical, yet understudied, subject by analyzing the associations between abusive parenting style, neighborhood characteristics, and MPD among youths in South Korea, a country with one of the highest mobile broadband penetration rates in the world. Based on the secondary analysis of two waves of Korean Children and Youth Panel Survey (KCYPS), a government-funded multiyear study, we investigate individual- and contextual-level factors underlying MPD. Findings show that, net of a host of time-lagged controls (including baseline dependency from the previous year), abusive parenting style significantly increases adolescent MPD. After adjusting for individual level characteristics, however, no contextual-level effect is found, i.e., residing in a neighborhood with a relatively higher proportion of parental abuse is not related to greater MPD. Finally, two cross-level interaction effects are observed. First, the association between parental abuse and MPD is weaker in a neighborhood context with better educated inhabitants (more college graduates). Second, it is reinforced in demographically "aged" communities with more elderly residents.